Faktor-Faktor Yang Mempengaruhi Pengelolaan Dana Desa (Studi Kasus Pada Desa Di Kecamatan Jepara) - Selfia Desty Laksmita Viani; Jaeni Jaeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the factors that influence the management of village funds in villages in Jepara District. The population determined in this study is the village apparatus working in Jepara District. Determination of the number of samples obtained using the Slovin formula, resulting in 66 respondents. The method for sampling is purposive sampling method. This type of research is quantitative research with Partial Least Square (PLS) analysis technique. The results showed that Accountability, Community Participation, Local Wisdom had a positive and insignificant effect on the management of village funds and Supervision, Village Apparatus Competence had a negative and insignificant effect on the management of village funds, and Transparency had a positive and significant effect on the management of village funds. Keywords: Accountability, Supervision, Community Participation, Village Official Competence, Transparency, Local Wisdom, Village Fund Management.